2018
DOI: 10.3390/foods7110182
|View full text |Cite
|
Sign up to set email alerts
|

Screening Method to Evaluate Amino Acid-Decarboxylase Activity of Bacteria Present in Spanish Artisanal Ripened Cheeses

Abstract: A qualitative microplate screening method, using both low nitrogen (LND) and low glucose (LGD) decarboxylase broths, was used to evaluate the biogenic amine (BA) forming capacity of bacteria present in two types of Spanish ripened cheeses, some of them treated by high hydrostatic pressure. BA formation in decarboxylase broths was later confirmed by High Performance Liquid Chromatography (HPLC). An optimal cut off between 10–25 mg/L with a sensitivity of 84% and a specificity of 92% was obtained when detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Later, Ladero et al [50] suggested that tyramine biosynthesis is actually a species-level characteristic trait of E. faecium, E. durans, and E. faecalis, which we also confirmed in this study. Similarly, levels of tyramine ranged from 99.1 to 3664.7 mg/L within eight strains of the E. faecium/durans group cultured in modified BA broth media by Espinosa-Pesqueira et al [51]. Notably, both tyramine and histamine were not detected in the cultures of four strains of Lb.…”
Section: Discussionmentioning
confidence: 90%
“…Later, Ladero et al [50] suggested that tyramine biosynthesis is actually a species-level characteristic trait of E. faecium, E. durans, and E. faecalis, which we also confirmed in this study. Similarly, levels of tyramine ranged from 99.1 to 3664.7 mg/L within eight strains of the E. faecium/durans group cultured in modified BA broth media by Espinosa-Pesqueira et al [51]. Notably, both tyramine and histamine were not detected in the cultures of four strains of Lb.…”
Section: Discussionmentioning
confidence: 90%
“…In terms of the functional relationship between bacterial communities and BAs production, Lactobacillus was strongly positively correlated with most of the identified BAs, while Chromohalobacter was positively correlated with MEA. SLAB, NSLAB and other microorganisms have been reported as decarboxylase-producing bacteria [ 28 , 126 ], which has been proven for several Lactobacillus strains, for example, L. acidophilus PNW3 [ 127 , 128 , 129 , 130 ], including halotolerant Lactobacillus species [ 131 , 132 ]. Body et al [ 133 ] have reported the higher the salt concentration (up to 3%) the higher BAs production by L. reuteri strains, which is consistent with the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous polyamines in foods are usually absorbed before they reach the large bowel (Ramos-Molina et al . 2019 ), so it is likely that an important share found in feces was synthesized in the gut by decarboxylase-positive microorganisms such as Enterobacteriaceae, Enterococcus, E. coli and lactic acid bacteria (Espinosa-Pesqueira, Roig-Sagues and Hernandez-Herrero 2018 ). Putrescine, spermine and spermidine derive from l -arginine or l -ornithine depending on the microorganism involved, and the degradation and recycling of biogenic amines comprise, among others, the conversion of putrescine into spermine and this into spermidine and vice-versa (Fernandez-Reina, Urdiales and Sanchez-Jimenez 2018 ).…”
Section: Discussionmentioning
confidence: 99%